Advantages and disadvantages of distance learning - Vlasenko, Ludmila; Bozhok, Natalia (My University, 2014)
The article defines the issues of distance education in modern society, the foreign language learning in this aspect and the necessity of Internet facilities development in the system of professional study.
Keywords: distance education; advantages; professional activity; дистанційне навчання; професійна діяльність; кафедра ділової іноземної мови та міжнародної комунікації